IMPROVING STUDENTS' PRONUNCIATION ABILITY IN SPEAKING USING "HELLO ENGLISH" APPLICATION - Seflianti, Seflianti; Luardini, Maria Arina; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2019)
This Collaborative Classroom Action Research was conducted to know the use of “Hello English” (HE) application to improve the students’ pronunciation ability in speaking. The subject and setting of the research were Speaking 2 students of English Education Study Program, University of Palangka Raya. The data were collected in form qualitative and quantitative data. The qualitative data were obtained from the result of questionnaire on the use of HE application, and the quantitative data were taken from the test results to know the students’ pronunciation ability in speaking. The result shows that the mean score of PreAction Test of 52.3 was lower than the minimum mean score 70. The data of cycle 1 show that the students’ mean score was higher than minimum mean score (92.0) but there were some students who still had “fair” interest, activities, and ability when using HE application, which means one of the criteria of success was not passed and need some improvement in cycle 2. The results in cycle 2 show that the students’ mean score was higher than minimum mean score (94.3) and all the students had “good” and “excellent” interest, activities and ability when using HE application. It can be concluded that “Hello English” application can improve the students’ pronunciation ability by practicing it several times.